A lever concept integrated with simple rules for flow shop scheduling. Issue 11 (3rd June 2017) - Li, Wei; Freiheit, Theodor; Miao, Enming
Abstract : The development of more efficient and better performing priority dispatching rules (PDRs) for production scheduling is relevant to modern flow shop scheduling practice because they are simple, easy to apply and have low computational complexity, especially for large-scale problems. While the current research trend in scheduling is towards finding superior solutions through meta-heuristics, they are computationally expensive and many meta-heuristics also use PDRs to generate starting points. In this paper, we analyse the properties of flow shop scheduling problems to minimise maximum completion time, and generate a new dominance rule that is complementary to Szwarc's rule. These dominance rules indicate that a weighting factor should be included in sequencing to account for the possibility that a single job's processing time can generate idle time repeatedly within a flow line. Two new PDRs with a leveraged weighting factor are proposed to minimise makespan and average completion time. Computational results on Taillard's benchmark problems and on historical operating room data show that the proposed PDRs perform much better than established PDRs without an increase in computational complexity.